Creep behavior of concrete elements strengthened with NSM CFRP laminate strips under different environmental conditions - Sena-Cruz, José (2013)
The present work intends to contribute for the knowledge on the long-term deformational performance of concrete structures strengthened with the near-surface mounted (NSM) technique. For that purpose a wide experimental program has been initiated using beam pullout and slab specimens submitted to sustained loads under the following environmental conditions: (i) 20ºC temperature and 55% relative humidity; (ii) immersed in water tank at 20ºC with 0% of chlorides; (iii) immersed in water tank at 20ºC with 2.5% of chlorides; (iv) submitted to wet/dry cycles at 20ºC with 2.5% of chlorides. The slabs are continuously monitored in terms of mid-span vertical deflection and strains (in concrete, CFRP laminate strip and steel reinforcements), whereas for the case of the beam pullout specimens monitoring includes the free and loaded end slips and strain in CFRP laminate strip. The present paper summarizes the preliminary results.